2012
DOI: 10.1037/a0025470
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between trauma and forgiveness in post-conflict Sierra Leone.

Abstract: The decade-long civil war in Sierra Leone was declared over in 2002, but the psychological impact of the conflict remains. The purpose of this study was to determine if forgiveness is related to improved adjustment to trauma and for what demographic groups it is most useful in postwar Sierra Leone. Data were collected as part of the Association for Trauma Outreach and Prevention of Meaningfulworld's humanitarian outreach mission to Sierra Leone in March of 2009. Participants were administered a sociodemographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
6
20
1
Order By: Relevance
“…In this review, one study reported a statistically significant inverse relationship between overall forgiveness and trauma symptom severity in this group, with older women showing the strongest association across groups (Doran et al, 2012). This finding needs to be explored in further research, especially as the older age group is underrepresented in this systematic review.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In this review, one study reported a statistically significant inverse relationship between overall forgiveness and trauma symptom severity in this group, with older women showing the strongest association across groups (Doran et al, 2012). This finding needs to be explored in further research, especially as the older age group is underrepresented in this systematic review.…”
Section: Discussionmentioning
confidence: 96%
“…PTSD disorders were significantly higher among participants with low forgiveness scores. A study conducted in Sierra Leone exploring the psychological impact of the civil war showed a different result: No significant correlation was found between overall forgiveness and traumatic stress (Doran et al, 2012).…”
Section: Trauma At Intergroup Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…Research reveals that interventions that promote forgiveness can be effective in promoting mental and physical health (Baskin & Enright 2004, Hui & Chau 2009, Reed & Enright 2006, Waltman et al 2009) in adults and children dealing with interpersonal wrong, conflict or emotional abuse. There has also been interest in the role of forgiveness in the context of ethnic and civil conflicts in places such as Rwanda and Sierra Leone (Doran et al 2012). In Rwanda, for example, a forgiveness intervention was associated with reduced trauma symptoms and a more positive orientation toward members of the other group (Staub et al 2005).…”
Section: Emerging Areas Of Interestmentioning
confidence: 99%